ROLE OF FINANCIAL MANAGEMENT IN ENTERPRISE MANAGEMENT - К.О. Shayakhmetova; G.I. Nesterenko; B. G. Iskakova; G.К. Ahonova; N.R. Rakhimberdina (Academic Journal of Physical and Chemical Sciences, 2019)
This article discusses the process of managing the financial activities of an enterprise, which is based on a specific mechanism and represents a combination of the main elements of influence on the process of developing and implementing management decisions. An effective financial management mechanism allows to realize the goals and objectives it faces fully, contributes to the effective implementation of the functions and principles of enterprise financial management.